Leukemic retinopathy, a rare entity: A case report - Gupta, Aman Kumar; Basnet, Rakshya; Yadav, Roshan Dev; Singh, Sweta (Asian Journal of Medical Sciences, 2021)
Chronic myelogenous leukemia (CML), also known as chronic myeloid leukemia, is a myeloproliferative disorder characterized by increased proliferation of the granulocytic cell line without the loss of their capacity to differentiate. Consequently, the peripheral blood cell profile shows an increased number of granulocytes and their immature precursors, including occasional blast cells. CML accounts for 20% of all leukemias affecting adults. Retinal lesions are the most common ocular manifestation of leukemia. They are found most often in adults and in patients with myeloid leukemia. Despite the significant efforts made by different groups to optimize treatment and outcome, there are still unmet needs and unanswered questions. Ophthalmologic manifestations are among the therapeutic challenge. Here we present a case of CML (chronic phase) with ophthalmologic manifestations as initial presentation, trying to shed light on this important type of presentation.